On the Search for a Tripartite Identity: Paule Marshall’s Upward Mobility Narrative in Praisesong for the Widow - Courtney Walton (Angles)
Paule Marshall’s Praisesong for the Widow (1983) follows the post-Civil Rights Movement, African American literary trend of presenting methods of black characters resisting white supremacy through an embrace of black culture and black life. It is through Marshall’s main character, Avey, that readers can see this tortuous, but fulfilling progression towards self-discovery. In Avey’s journey, she experiences “Rememory,” which leads to a reconnection to her tripartite identity, or reclamation to her American and Caribbean roots. Avey's path to understanding her complete self is accelerated through her visit to Grenada and Carriacou coupled with her memories of her time in Brooklyn, New York; and her childhood memories with the Gullah peoples of South Carolina. This embrace of her three-part identity is not simplistic nor straightforward but reveals the necessity for community within the African diaspora, in part because of the many injustices faced by Black Americans. Praisesong for the Widow uses Avey’s husband, Jay, also known as Jerome, to show the effects of constant discrimination within the workforce. However, after years of trying, Jerome does manage to advance professionally, but not without a hefty price. Directly through the characterization of Avey and Jerome and the inclusion of an upward mobility narrative, Marshall’s novel provides commentary and a warning to those who turn away from black cultural communities. Through an examination of the upward mobility narrative and Marshall’s advocation for cultural nationalism, this article will unearth the seriousness of discrimination within the professional world and the potentially devastating effects on identity and self-actualization.